Symptomatology and diagnosis of the new coronavirus: a systematic review (Research, Society and Development, 2020)
Introduction: The disease called COVID-19 or 2019-nCoV, started in 2019, in Wuhan, China. According to international data, obtained on August 22, 2020, Brazil ranks 2nd in the number of confirmed cases and 2nd in the number of deaths. Coronavirus is a current and urgent health problem that has a worldwide distribution. Objective: The objective of this work is to carry out a systematic review, showing the main symptoms and the diagnosis of COVID-19. Methodology: This is a systematic review, using databases from the BVS, SCIELO, SCIENCEDIRECT and MEDLINE, LILACS. Results and Discussion: The symptoms of COVID-19 cases vary between mild and severe cases. Rapid tests are used to detect IgM and IgG antibodies using the lateral flow chromatography methodology, which can be used in the tests: plasma, serum and the patient's whole blood. Detection of the virus by RT-PCR in real time is the gold standard in its identification, being the test for symptomatic patients in the acute phase, its diagnosis has high sensitivity and specificity. Conclusion: This research highlights the importance of laboratory tests for the accurate diagnosis of COVID-19, with the RT-PCR test being the most suitable for the detection of SARS-CoV-2.